Risks and Legal Protection in Non-Cash Financial Transactions Through E-Wallets - Oriento, Cahyo; Negara, Dharma Setiawan; Putra, Arif Rachman; Arifin, Samsul; Saputra, Rio (Journal of Social Science Studies, 2023)
The application of legal protection in non-cash financial transactions through e-wallets has become important as technology develops and the number of users of this service increases in Indonesia. Although facilitating transactions, e-wallets carry risks such as misuse of personal data and fraud. Proper legal protection is needed to ensure transaction security and protect consumers. Existing regulations, such as the Electronic Information and Transaction (ITE) Law, and Financial Services Authority (OJK) Regulations, provide a legal foundation, but there are still challenges in supervision and implementing regulations in line with technological developments. Strengthening supervision, improving digital literacy, and transparency from service providers are key to mitigating risks. Effective legal protection can increase public trust in financial technology and support financial inclusion. Adaptive policies and collaboration between relevant parties are needed to ensure a safe and fair digital ecosystem.